Occipitalization of atlas - A case report - Saranya Deb Barma; Gunamani Rabha; Kunjalal Talukdar (Wolters Kluwer Medknow Publications, 2016)
The atlas vertebra articulates with the occipital bone of the skull by a pair of synovial joints. Occipitalization is a congenital fusion of the atlas to the base of the occiput which reduces the foramen magnum dimension leading to neurological complications due to compression of spinal cord. Individuals with occipitalization of the atlas may have low hairline, torticollis, restricted neck movements and abnormal short neck. During routine osteology demonstration class for undergraduate students, a total atlanto-occipital fusion was seen. The clinical implications of atlanto- occipitalization may be beneficial for neurosurgeons, neurologists, orthopaedic surgeons and radiologists in day-to-day clinical practice